Hubungan Antara Pola Pemberian Makanan, Asupan Energi dan Zat Gizi Makro dengan Status Gizi Balita Usia 25–59 Bulan di Desa Karangasri Kabupaten Ngawi - Adella Anggyta Maynaputri; Choirul Anna Nur Afifah (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Feeding patterns are the efforts and ways of mothers in providing nutritional intake to toddlers so that the nutritional intake needs of toddlers are well met. The purpose of this study was to determine the relationship between feeding patterns with energy intake and macronutrients for toddlers aged 25-59 months in Karangasri Village, Ngawi Regency and the relationship between feeding patterns, energy intake and macronutrients with the nutritional status of toddlers aged 25-59 months in Karangasri Village, Ngawi Regency. The method in this study is a correlational quantitative study with a cross sectional approach. The sample of this study amounted to 80 respondents who were taken with convenience sampling technique. Data collection used Child Feeding Questionnaire (CFQ) for feeding pattern, SQ-FFQ Form for energy and macronutrient intake, weight and height measurement for nutritional status. Data were analyzed using Chi-Square and Rank Spearman tests. The results showed that there was a relationship between feeding patterns (p<0.05) with energy intake and macronutrients of toddlers and there was a relationship between feeding patterns (p=0.000), energy intake (p=0.001), carbohydrates (p=0.000), protein (p=0.002), and fat (p=0.001) with the nutritional status of toddlers. Mothers or guardians of toddlers are expected to maintain proper feeding patterns for toddlers and pay attention to toddler food intake by providing nutritious and balanced foods that suits the needs of toddlers.